The Bing plane and separately continuous mappings (in Ukrainian) - O. O. Karlova; V. K. Maslyuchenko; O. D. Myronyk (Математичні Студії)
We prove that the Bing plane $mathbbB$ is a$sigma$-metrizable but not strongly $sigma$-metrizable. Alsowe show that for $c$-connected topological spaces $X$ and $Y$each separately continuous function $fcolon Ximes YomathbbB$ is constant.